Cultivating Trust in the Face of Crisis: Science as Moderator in Collaborative Forest Management - Campbell, Emily B. (SocietàMutamentoPolitica, 2024)
How is conflict over resources managed in the context of ecological, economic, and political crisis? Trust is noted by scholars as fundamental for collaborative forest management (CFM), a shared governance tool that brings together different stakeholders. This paper extends the literature on trust by foregrounding the use of science to lead decision making processes in the face of crisis. Through a case study of a CFM partnership in the American west, the analysis examines a once feuding group of political adversaries who decided to work together and “let the science lead.” The study examines how the partnership navigated economic crisis and historic wildfires against the backdrop of longstanding regional conflict termed the timber wars. The science-led governance model described includes science-led decision making, ongoing research on forest treatments, and communication of scientific findings to partners. The partnership’s approach, undergirded by relational and procedural trust, highlights the socio-political and relational dimensions of science-informed, sustainable resource management. The findings of this study have implications beyond CFM as they point to the importance of relational trust building in civic science. Generating buy-in and collaboration, especially among those with little to no formal science background, is especially pertinent given the polarization of science more broadly.